1997
DOI: 10.1088/0264-9381/14/5/032
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic equilibrium of two spherical charged masses in general relativity

Abstract: Approximate solutions representing the gravitational-electrostatic balance of two arbitrary point sources in general relativity have led to contradictory arguments in the literature with respect to the condition of balance. Up to the present time, the only known exact solutions which can be interpreted as the non-linear superposition of two spherically symmetric (Reissner-Nordström) bodies without an intervening strut has been for critically charged masses,In the present paper, an exact electrostatic solution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…This simplicity permits us to prove a validity of conjectures of the papers [9] and [16] on exact analytical level. It allows also a direct analytical investigation of the physical properties of the equilibrium state of two non-extreme sources.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…This simplicity permits us to prove a validity of conjectures of the papers [9] and [16] on exact analytical level. It allows also a direct analytical investigation of the physical properties of the equilibrium state of two non-extreme sources.…”
Section: Introductionmentioning
confidence: 81%
“…Up to 1997 it remained unknown whether the analogous generalization for the non-extreme bodies can be found. The first solid arguments in favour of existence of a static equilibrium configuration for the "black hole -naked singularity" system was presented in [16]. These results have been obtained thereby numerical calculations and three examples of numerical solutions of the equilibrium equation have been demonstrated.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although it has been conjectured [5] that an exact solution under the condition (2) should exist in general relativity, in the (2nd) post-Newtonian approximation (2) is incompatible with the static balance condition [6], and a test particle analysis [7] suggested that (2) is neither necessary nor sufficient. This suggests a wider range of possibilities for realizing equilibrium in general relativity that do not exist non-relativisitically, and several numerical studies [8,9] have been carried out to this end. Until now no one has yet found -in any relativistic theory of gravity -equilibrium states in which √ 4πGm i > e i for both bodies.…”
mentioning
confidence: 99%
“…It is then straightforward to obtain an exact expression for r as a function of τ by inserting the expression for p(τ ) into (8) and solving for r as a function of τ . A number of different types of motion are possible, depending upon a combination of four factors: gravitational attraction, the electric force between charges, the effect of the cosmological constant and relativistic effects.…”
mentioning
confidence: 99%